PENGARUH CITRA MEREK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE DI KOTA TABANAN PADA MASA PANDEMI COVID-19 - Reinaldi Wiranata; Luh Komang Candra Dewi (Journal Research of Management, 2022)
This study aims to determine and analyze the influence of brand image, price and promotion on smartphone purchasing decisions in Tabanan City during the Covid-19 pandemic. The sampling technique used in this study is purposive sampling with the criteria of age, gender and brand purchased by respondents, namely people who buy smartphone products in Tabanan City. The data collection technique used is a questionnaire distributed using google form to 100 respondents. The analysis technique in this research is descriptive analysis, validity and reliability test, classical assumption test, multiple linear regression test, and t test analysis. Multiple linear regression analysis using SPSS 20 software for windows. The results of this study indicate that: Brand Image has a positive and partially significant influence on smartphone purchasing decisions in Tabanan City during the Covid-19 pandemic. Price has a positive and significant influence partially on smartphone purchasing decisions in Tabanan City during the Covid-19 pandemic. Promotion has a positive and significant influence partially on smartphone purchasing decisions in Tabanan City during the Covid- 19 pandemic. The implication of this research is that the company should maintain brand image, price and promotion because it can improve smartphone purchasing decisions and improve more sophisticated and attractive technology on smartphone products that will be sold in the future